Industrialisation in Modern Turkey and the Search for Environmental Justice for the Romani Population of the Ergene River Basin: Romani Voices amid Environmental Degradation - Sergen Gül (Critical Romani Studies)
This study examines the environmental injustices faced by Romani communities in Turkey’s Ergene River Basin, analysing the intersection of industrialisation, modernisation policies, and historical exclusion. It explores how legal frameworks, from the Ottoman period through to the early Republican years of Turkey and up to 2006, have contributed to the social and spatial marginalisation of Romani communities. Specifically, the paper problematises the disproportionate environmental burdens placed on the Romani population living along the Ergene River resulting from neoliberal industrial practices since the 1980s. A historical analysis is adopted by drawing on biographical narratives of Roma about the “Dead” Ergene River, along with archival records, data on environmental degradation, and legal documents. Findings highlight how Turkey’s modernisation and neoliberal industrialisation policies have led to environmental injustice for Romani communities, characterised by the unrecognised environmental risks they face and the unfair distribution of environmental harm. The study fills a gap in the literature by addressing the intersection of ethnic  discrimination and environmental degradation, framing the Ergene River Basin case within the context of environmental racism. It also contributes to broader discourses on environmental justice by advocating for more inclusive environmental policies that consider the historical and social vulnerabilities of marginalised communities.